Hydrophilic interactions; their Origin, their Magnitude and their Relevance to Protein Folding (JOURNAL OF ADVANCES IN CHEMISTRY, 2007)
A simple model is constructed in which the phenomenon of hydrophilic ( ) interactions may be studied exactly. This model reveals the origin of the strong interaction, as well as providing an approximate method of estimating its order of magnitude. The results are in agreement with previous theoretical calculations, as well as with experimental data, and simulated calculations. The source of the non-additivity of the interactions among three and four groups is examined. A few comments on the relevance of the interactions to the process of protein folding are discussed.